PENINGKATAN PERKEMBANGAN SOSIAL MELALUI GOBAK SODOR USIA 5-6 TAHUN DI TK ANUGRAH SUNGAI AMBAWANG - Maisaroh, Maisaroh; Syukri, Syukri; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn general, the purpose of this study is to determine the success of teachers improve the quality of learning process using gobak sodor game method to improve the social development in children aged 5-6 years in kindergarten Anugrah in the Ambawang river district. This research using Class Action Research, which is one of the problem solving strategy utilizing real action and capacity building process in detecting and solving problems. Based on the result of data analysis and research question in general can be concluded that learning using gobak sodor game method can improve the social development in children aged 5-6 years in kindergarten Anugrah in the Ambawang river district. It is based on the result of learning planning made by teachers to improve the social development of children's manners reached the category of 'Good' with a score of 3.67. Implementation of learning conducted by teachers in improving the social development of children's through the method of gobak sodor game reached the category of "Good" with a score of 3.76. The gobak sodor game method applied by teachers in learning can improve the behavior of children's manners this is shown by 97% children develop as expected.Â Keywords: Social Skill, Method of Gobak Sodor gameÂ